Corneal sensory nerve loss induced by repeated subconjunctival and topical bupivacaine disrupts tear secretion and enhances bacterial adhesion via neuropeptide modulation - Ananya Datta; Grace Kelly Orallo; Nahomy Nelson (PLoS ONE, 2025)
Purpose Corneal sensory innervation plays a crucial role in maintaining ocular surface integrity and immune homeostasis by regulating neuropeptide secretion in tear fluid. Sensory dysfunction disrupts tear production and neuropeptide signaling, increasing susceptibility to microbial infections. However, the mechanistic link between sensory nerve suppression, neuropeptide depletion, and bacterial adhesion remains incompletely understood. This study establishes a refined protocol for targeted corneal sensory nerve suppression using bupivacaine, a long-acting local anesthetic, and investigates the roles of substance P (SP) and calcitonin gene-related peptide (CGRP) in modulating tear production and bacterial adhesion. Method Male and female C57BL/6J (wild-type) mice (6–8 weeks old) were used to establish a localized and sustained corneal nerve suppression model via subconjunctival bupivacaine injection combined with topical application every other day for 15 days. This approach ensured precise modulation of corneal sensory function. Using this model, we investigated how sensory denervation influences microbial adhesion dynamics for Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis, three clinically relevant pathogens with distinct adhesion mechanisms. Bacterial inoculation was standardized using the Kimwipe blotting method to achieve uniform deposition onto the corneal surface, followed by quantification of bacterial adhesion. Tear production was assessed using SMTube testing to evaluate nerve depletion-associated alterations. Enzyme-linked immunosorbent assay (ELISA) was used to quantify SP and CGRP levels in tear fluid, determining whether their depletion correlated with increased bacterial adhesion and altered tear production. To assess whether neuropeptide restoration mitigates bacterial adhesion, SP, CGRP, or phosphate-buffered saline (PBS; control) was administered via subconjunctival injection prior to bupivacaine treatment on day 14 and 15 during the experimental timeline. All assessments, including nerve depletion effects on tear production, bacterial adhesion, and neuropeptide loss, were conducted on day 15 post-bupivacaine treatment. Results Targeted corneal sensory denervation via combined subconjunctival and topical bupivacaine resulted in a ~ 50% reduction in corneal nerve density, achieving deeper and more localized nerve suppression compared to subconjunctival injection alone (P < 0.0001). This approach led to a 2.3-fold (~56.6%) reduction in tear production without inducing epithelial damage (P < 0.0001). This loss of sensory input led to a marked decrease in SP and CGRP levels in both the cornea and tear fluid, with the most pronounced reduction observed in the combined treatment group. Notably, neuropeptide depletion correlated with increased bacterial adhesion, with a ~ 1.18-fold increase for S. aureus and ~1.20-fold for P. aeruginosa, highlighting the critical role of corneal sensory nerves in modulating ocular surface immunity (P < 0.0001). Exogenous SP or CGRP supplementation restored neuropeptide levels and CGRP supplementation reversed bacterial adhesion, highlighting their critical function in maintaining antimicrobial defense. Conclusion This study establishes a novel, controlled model of corneal sensory denervation, revealing a direct link between neuropeptide depletion, impaired tear production, and increased microbial adhesion. By simulating neuropathic conditions such as diabetic keratopathy and neurotrophic keratitis, this approach provides a valuable framework for investigating neuroimmune interactions in ocular infections. Beyond infection models, this subconjunctival injection strategy serves as a versatile platform for studying ocular drug pharmacokinetics, neuroprotective interventions, and immune modulation.